2016
DOI: 10.20341/gb.2015.018
|View full text |Cite
|
Sign up to set email alerts
|

The Kulm Facies of the Montagne Noire (Mississippian, southern France)

Abstract: ABSTRACT. The Kulm facies of the Montagne Noire formed in a foreland basin south of the French Massif Central. During the preorogenic phase (Tournaisian -early late Viséan) two major facies domains can be differentiated in the Montagne Noire. The Mont Peyroux Succession represents more distal environments with an almost continuous stratigraphical record, which displays the development from a deeper-water carbonate platform to a starved basin facies, which is followed by the onset of calciturbidite deposition. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 17 publications
1
16
0
Order By: Relevance
“…Recent studies documented positive excursions in nitrogen and sulphur isotopes in South China and North America, suggesting enhanced water-column denitrification and sulphate reduction respectively, under increased organic carbon burial and expansion of oxygen minimum zone (Yao et al, 2015;Maharjan et al, 2018a, b). In addition, mid-late Tournaisian black shales developed on shallow platforms and slopes in South China and southern Laurussia (Yao et al, 2015;Aretz, 2016), which further supports the notion of increased organic burial rates at this time. Enhanced organic burial could have resulted in atmospheric CO2 drawdown and climate cooling (Mii et al, 1999;Yao et al, 2015), consistent with positive oxygen isotopic excursion during the TICE interval (Mii et al, 1999;Buggisch et al, 2008;Grossman et al, 2008;Fig.…”
Section: Marine Anoxiasupporting
confidence: 65%
See 1 more Smart Citation
“…Recent studies documented positive excursions in nitrogen and sulphur isotopes in South China and North America, suggesting enhanced water-column denitrification and sulphate reduction respectively, under increased organic carbon burial and expansion of oxygen minimum zone (Yao et al, 2015;Maharjan et al, 2018a, b). In addition, mid-late Tournaisian black shales developed on shallow platforms and slopes in South China and southern Laurussia (Yao et al, 2015;Aretz, 2016), which further supports the notion of increased organic burial rates at this time. Enhanced organic burial could have resulted in atmospheric CO2 drawdown and climate cooling (Mii et al, 1999;Yao et al, 2015), consistent with positive oxygen isotopic excursion during the TICE interval (Mii et al, 1999;Buggisch et al, 2008;Grossman et al, 2008;Fig.…”
Section: Marine Anoxiasupporting
confidence: 65%
“…In the shallow water, carbonate production slowed down or ceased, and black-greyish shales, marls and marly limestones were deposited, which indicate dysoxic to occasionally anoxic conditions (e.g., Poty et al, 2002Poty et al, , 2011Yao et al, 2015). This marine anoxia is also evidenced by isotopic records (e.g., Yao et al, 2015;Aretz, 2016;Maharjan et al, 2018b). A major, positive shift in inorganic carbon isotope occurred in the mid-Tournaisian, named as the "Tournaisian Carbon Isotope Excursion" (TICE; Yao et al, 2015;Fig.…”
Section: Marine Anoxiamentioning
confidence: 95%
“…1A) which are generally interpreted as olistoliths and flysch, respectively. Several authors demonstrated that these successions are late Viséan to early Serpukhovian in age (Böhm 1935;Gèze 1949;Mamet 1968;Vachard 1974aVachard , b, 1977aEngel et al 1982;Feist & Galtier 1985;Poty et al 2002;Aretz 2002Aretz , 2016Vachard & Aretz 2004;Korn & Feist 2007;Pille 2008;Vachard et al in press). The eight foraminiferal regional biozones of Vachard et al (in press) significantly refine the stratigraphic frame for the Viséan-Serpukhovian boundary interval in the Montagne Noire.…”
mentioning
confidence: 99%
“…The top of the Roc de Murviel Formation is transitional into shales and oolitic beds of the La Serre de Péret Formation. That formation is considered to have been deposited mostly in deltaic environments and can be correlated to the deltaic siliciclastic successions located west of Cabrières town (Aretz, ; Vachard et al ., ).…”
Section: Stratigraphical and Sedimentological Contextmentioning
confidence: 99%